2001
DOI: 10.1111/j.8755-8920.2001.450506.x
|View full text |Cite
|
Sign up to set email alerts
|

Murine Stress‐triggered Abortion is Mediated by Increase of CD8+ TNF‐α+ Decidual Cells via Substance P

Abstract: Our data suggest that stress-triggered abortion is mediated by SP, and SP receptor blockade abrogates stress-triggered abortion via reduced production of TNF-alpha by CD8+ T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
66
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 21 publications
4
66
2
Order By: Relevance
“…The "Th1/Th2 paradigm" proposes that Th2-type cytokines such as IL-4 and IL-10 may favor the maintenance of mammalian pregnancy [6,[10][11][12], whereas the excessive production of Th1 cytokines (IL-2, IFN-c, TNF-a) would mediate the rejection of the fetus at the feto-maternal interface [10,[13][14][15][16][17]. Thus, we wondered whether the protective effects observed after transfer of pregnancy-induced Treg were related to a down-regulation of "abortive" cytokines (Th1) and/or to an up-regulation of pregnancy-protective (Th2) cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The "Th1/Th2 paradigm" proposes that Th2-type cytokines such as IL-4 and IL-10 may favor the maintenance of mammalian pregnancy [6,[10][11][12], whereas the excessive production of Th1 cytokines (IL-2, IFN-c, TNF-a) would mediate the rejection of the fetus at the feto-maternal interface [10,[13][14][15][16][17]. Thus, we wondered whether the protective effects observed after transfer of pregnancy-induced Treg were related to a down-regulation of "abortive" cytokines (Th1) and/or to an up-regulation of pregnancy-protective (Th2) cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Th1/Th2 cytokine balance with Th2 predominance has been seen as a very important mechanism determining the survival of the fetus in the maternal uterus [6][7][8][9][10][11][12][13][14][15][16][17]. However, mice genetically deficient for IL-4 and IL-10 do not show disturbed pregnancy [18], suggesting that Th2 cells are not essential for normal pregnancy and alloreactive Th1 cells must be differently regulated, as already proposed [19][20][21].…”
Section: Introductionmentioning
confidence: 96%
“…Hence, it has been suggested that plural tolerance mechanisms have evolved to ensure the maintenance of the feto-placental graft. Such mechanisms include the following: 1) the predominance of anti-inflammatory, Th2 cytokines over proinflammatory Th1 cytokines in the decidua (3)(4)(5); 2) the decidual expression of indoleamine 2,3-dioxygenase (IDO), 3 an enzyme that famishes immune rejection by depriving the T cells of tryptophan and/or by inhibiting lymphocyte proliferation (6 -8); 3) the presence of CD4 ϩ CD25 bright regulatory T (Treg) cells, which suppress an aggressive allogeneic response directed against the fetus, as simultaneously described in human pregnancies by the Saito group (9) and in murine pregnancies (10); and 4) the synthesis of asymmetric IgG Abs (AAbs), which have been suggested to camouflage paternal Ags expressed by the placenta (11)(12)(13). In addition, it has become apparent in the past few years that dendritic cells (DCs) seem to be an essential regulatory cell subset at the feto-maternal interface in mediating tolerance (14 -16).…”
mentioning
confidence: 99%
“…Furthermore, the verdict of survival or rejection of the fetus is partially dependent on the events endangering the mother, prevalently environmental parameters such as exposure to psychoemotional stress (5). Based on their importance in both cell recruitment and cross talk with APC, LFA-1 and ICAM-1 molecules may become attractive targets for developing new therapies to facilitate fetal tolerance by preventing rejection pathways during pregnancy, e.g., triggered by stress exposure.…”
mentioning
confidence: 99%
“…Such signals that exceed intrinsic built-in thresholds trigger the rejection process, inducing a miscarriage. Stress-triggered miscarriages have been widely reported in the literature (12)(13)(14). In contrast, it is known that glucocorticoid hormones are the major responders to various stresses, but tightly regulated for functional exertion.…”
mentioning
confidence: 99%